2010
DOI: 10.1161/circimaging.109.918482
|View full text |Cite
|
Sign up to set email alerts
|

Rapid 3D Phenotyping of Cardiovascular Development in Mouse Embryos by Micro-CT With Iodine Staining

Abstract: Background-Microcomputed tomography (micro-CT) has been used extensively in research to generate high-resolution 3D images of calcified tissues in small animals nondestructively. It has been especially useful for the characterization of skeletal mutations but limited in its utility for the analysis of soft tissue such as the cardiovascular system. Visualization of the cardiovascular system has been largely restricted to structures that can be filled with radiopaque intravascular contrast agents in adult animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
295
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(302 citation statements)
references
References 33 publications
3
295
2
2
Order By: Relevance
“…A persistent challenge, however, was the limited ability to visualize and quantify soft tissues using Micro-CT. We and others have overcome this limitation with the optimization of osmium tetroxide (OT) as a CT dense contrast agent, showing dramatic visualization capability in mouse embryos without altering specimen geometry (Johnson et al, 2006;Metscher, 2009;Degenhardt et al, 2010). This study complements these by quantitatively analyzing embryonic chick morphogenesis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A persistent challenge, however, was the limited ability to visualize and quantify soft tissues using Micro-CT. We and others have overcome this limitation with the optimization of osmium tetroxide (OT) as a CT dense contrast agent, showing dramatic visualization capability in mouse embryos without altering specimen geometry (Johnson et al, 2006;Metscher, 2009;Degenhardt et al, 2010). This study complements these by quantitatively analyzing embryonic chick morphogenesis.…”
Section: Discussionmentioning
confidence: 93%
“…More recently, we demonstrated using osmium tetroxide (OT) as a diffusive CT contrast agent that high resolution detailed visualization and segmentation of rodent embryos to newborns was possible with Micro-CT; these previous studies included early stage mouse and rabbit embryos (Johnson et al, 2006;Carney et al, 2007;Martinez et al, 2009). Investigators have since followed with related studies in model organisms to explore the effects of different chemical agents on soft tissue contrast enhancement (Metscher, 2009;Degenhardt et al, 2010).…”
mentioning
confidence: 99%
“…Metscher (2009a) suggested that stains are usually not tissue‐specific and the final quality depended mainly on the fixative. However, comparisons between different stains have shown that indeed some compounds can stain lipidic tissue more intensely (e.g., Lugol's solution) (Degenhardt et al., 2010); thus, recognition of different tissues can be greatly influenced by the chosen stain (Smith et al., 2016). …”
Section: Preparation Of Samples For X‐ray Ctmentioning
confidence: 99%
“…PTA failed to stain the complete sample (neither head nor abdomen), and the few stained regions had very strong contrast, precluding adequate tissue recognition (Figure 4a‐d). The unstained parts of the samples exposed to PTA had minor contrast, resembling tissues that had not been exposed to any stain (Degenhardt et al., 2010; Metscher, 2009a), thus indicating that the tissue penetration was insufficient and samples would have to be exposed for more days to attain the desired stain.…”
Section: Experimental Comparison Of Staining and Fixation Approachesmentioning
confidence: 99%
“…Alternatively, rapid 3D phenotyping of cardiovascular development in mouse embryos has been achieved by ex vivo micro-CT with iodine staining (Degenhardt et al, 2010). In vivo micro-CT-based cardiac morphological and functional imaging in mice and rats has been reported using both PG and RG approaches (Badea et al, 2005(Badea et al, , 2008cBartling et al, 2007a,b;Detombe et al, 2008;Drangova et al, 2007;Nahrendorf et al, 2007;Song et al, 2007).…”
Section: Cardiac Imagingmentioning
confidence: 99%